Synergizing NOMA and energy harvesting in full duplex mobile edge computing for optimized energy efficiency - Mirza Baber Baig; Taoshen Li; Muhammad Zain Yousaf; Mohit Bajaj; Arvind R. Singh; Milkias Berhanu Tuka (Scientific Reports)
Abstract This research introduces a novel approach to enhance energy efficiency in Mobile-Edge Computing (MEC) systems by integrating Non-Orthogonal Multiple Access (NOMA) with energy harvesting in a full-duplex (FD) environment. The primary objective is to optimize edge computing performance while minimizing energy consumption. A comprehensive resource allocation strategy is proposed, considering CPU frequency, power control for both uplink and downlink, time scheduling, and data offloading. Mobile users can offload computationally demanding tasks to MEC servers via NOMA, promoting efficient data exchange. Full-duplex base stations simultaneously manage task offloading and energy transmission, improving resource utilization. A Block Coordinate Descent (BCD)-based algorithm addresses the non-convex optimization challenge, offering an optimal solution. Simulation results demonstrate that the NOMA-assisted FD-MEC system significantly outperforms traditional Orthogonal Multiple Access and Half-Duplex approaches, leading to improved energy efficiency and reduced energy consumption. This study highlights the potential of integrating NOMA, energy harvesting, and full-duplex technologies to create more energy-efficient MEC systems.